Analisis Yuridis Peningkatan Penanaman Modal Asing Di Kota Batam - Junimart Girsang; Lu Sudirman; Desy Susanti (Journal of Judicial Review, 2015)
Since the development of Batam in 1970 until today. Great progress has been achieved so far, by the end of 2013, Batam has accumulated a total of about US $ 16.47 billion. However, the increase in foreign investment in Batam do not necessarily make Batam as the main destination of foreign investment. Indonesia Investment Coordinating Board (BKPM) set a best of seven provincial investment sector "Regional Champioship" in 2011. Kepulauan Riau (Batam) are not included in the list issued by BKPM best. This is due to the dualism of leadership in Batam which give rise to a conflict of regulations produced by the Free Trade Zone Authority (BP Batam) and the governmentof Batam which create legal uncertainty for foreign investors and the establishment of one door integrated services are facing obstacles of coordination between institutions, this is due to the licenses investors related departments / agencies of government that has not been delegated to the authority permissions to the BKPM so that the effectiveness of the one stop service has not reached its full potential, and also labor turmoil that demands minimum wage increases that often culminate in a demonstration anarchists that threaten conduciveness foreign investment in Batam. This research is a normative juridical law, because the data to be retrieved and examined are the data obtained through the primary legal materials, namely Law No. 25 Year 2007 on Investment by using secondary law approach to the principles of law in Indonesia.